PLCε knockdown overcomes drug resistance to androgen receptor antagonist in castration‐resistant prostate cancer by suppressing the wnt3a/β‐catenin pathway. Issue 9 (26th January 2019) - Li, Luo; Du, Zhongbo; Gao, Yingying; Tang, Yu; Fan, Yanru; Sun, Wei; Li, Ting; Liu, Nanjing; Yuan, Mengjuan; Fan, Jiaxin; Niu, Lingfang; Yan, Jinxiao; et al.
Abstract: Most prostate cancers (Pcas) develop into castration‐resistant prostate cancer (CRPC) after receiving androgen deprivation therapy (ADT). The expression levels of PLCε and wnt3a are increased in Pca and regulate androgen receptor (AR) activity. However, the biological function and mechanisms of PLCε and wnt3a in CRPC remain unknown. In this study, we found that the expression levels of PLCε, wnt3a, and AR were significantly increased in CRPC tissues as well as bicalutamide‐resistant‐LNCaP and enzalutamide‐resistant‐LNCaP cells. In addition, PLCε knockdown partly restored the sensitivity of drug‐resistant cells to bicalutamide and enzalutamide by inhibiting the activity of the wnt3a/β‐catenin/AR signaling axis. Interestingly, the resistance of LNCaP cells docetaxel is related to PLCε but not the wnt3a/β‐catenin pathway. We also found that the combination of PLCε knockdown and enzalutamide treatment synergistically suppressed cell proliferation, tumor growth, and bone metastasis using in vitro and in vivo experiments. Our study revealed that PLCε is involved in the progression of drug‐resistance in CRPC and could be a new target for the treatment of CRPC. Abstract : Our results showed that the overexpression of PLCε induced the activation of the wnt3a/β‐catenin/androgen receptor (AR) axis, eventually leading to bicalutamide and enzalutamide resistance. Furthermore, wnt3a may be a potential biomarker to assess the type of drug resistance that will occur in patients with prostate cancer (Pca).